Assessment of natural gas/hydrogen blends as an alternative fuel for industrial heat treatment furnaces. (15th June 2021) - Mayrhofer, Markus; Koller, Michael; Seemann, Peter; Prieler, Rene; Hochenauer, Christoph
Abstract: The present study investigates the application of natural gas/hydrogen blends as an alternative fuel for industrial heat treatment furnaces and their economic potential for decreasing carbon dioxide emissions in this field of application. Doing so, a detailed technological analysis of several influencing parameters on the heating system was performed as well as a consideration of furnace heating technology challenges. Starting with an evaluation of the main thermophysical properties of the blends and their corresponding flue gases, requirements for the heating systems were identified. Potential ways of decreasing flue gas losses and increasing the heat transfer are shown. In the radiant tube application, an increased overall combustion efficiency of about 1.2% was measured at 40 vol% hydrogen in the fuel gas. Influences on the air to gas ratio control system of the furnace is a further important point, which was considered in this study. Two commonly used control systems were evaluated concerning their capabilities to regulate the gas flow rates of blends with varying hydrogen contents and combustion properties, such as Wobbe Index. This is important, since it shows the capability to retrofit existing furnaces. Two types of burners were tested with different natural gas/hydrogen blends. This includes an open jet burner with air-staged and flameless combustion operation modes. A recuperative burner for radiant tube application was considered as well in these tests. Doing so, the nitrogen oxide formation of both systems under different operating conditions and different fuel blends were evaluated. An increase by about 10% at air-staged combustion and about 100% at flameless combustion was measured by a hydrogen content of 40 vol% in comparison to pure natural gas firing. Finally, the additional fuel costs of natural gas hydrogen blends and different cases are presented in an economic analysis. The driving force for the use of hydrogen as a fuel is the price of the CO2 certificates, which are considered in the analysis at a current price of 25.2 €/t CO2. Highlights: Potential analysis of natural gas/hydrogen blends as fuel for heat treatment furnaces. Investigation of thermal efficiency depending on H2 enrichment. Effect of H2 enrichment on the air to gas ratio control systems. Thermal nitrogen formation at different operation modes and H2 enrichments. Economic aspects of natural gas/hydrogen blends.